Procedural technique for hybrid pulmonary valve replacement in infants and small children. (30th November 2020) - Breatnach, Colm R; McGuinness, Jonathan; Ng, Li Yen; Franklin, Orla; Redmond, Mark; Nölke, Lars; McMahon, Colin; Oslizlok, Paul; Walsh, Kevin; Kenny, Damien
Abstract: : OBJECTIVES: Hybrid approach to pulmonary valve replacement (PVR) in the paediatric population has been reported, although data in infants and small children are limited. Several strategies are now possible. The aim of this study is to review our hybrid PVR strategy in a complex patient cohort, outlining a variety of approaches employed in our centre. METHODS: We performed a retrospective review of infants and small children who underwent hybrid PVR between May 2017 and April 2019 in a single tertiary cardiology centre. Medical records were reviewed to ascertain demographic, clinical and outcome data. RESULTS: Ten patients with a median (interquartile range) age of 1.5 years (1.1–1.9) and weight of 8.8 kg (8–10.6) were managed with hybrid pulmonary valve insertion. Eight patients had perventricular approach (4 sternotomy and 4 subxiphoid) and 2 patients had surgically sutured valve. Six patients underwent cardiopulmonary bypass for associated lesions. Three had insertion of the valve into conduits and 7 were deployed into native right ventricular outflow tracts. The pulmonary valve was successfully inserted in all 10 patients with no mortality. Postprocedural complications included paravalvar leak in 2 patients, suspected endocarditis in 1 patient who developed early valve regurgitation and wound infection in 1 patient. CONCLUSIONS: Several approaches to hybrid PVR may be employed in small children with a high success rate. Follow-up studies are required to evaluate longer term durability of these approaches compared to standard surgical replacement.